2003
DOI: 10.1023/b:appa.0000005143.90681.82
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to flumethrin in the Mexican Aldama strain of the cattle tickBoophilus microplus(Acari: Ixodidae)

Abstract: The objective of this study was to evaluate the inheritance mode of resistance to flumethrin in the Mexican Aldama Boophilus microplus strain. Two Mexican strains were used, the Chiapas susceptible (SS), and the Aldama flumethrin-resistant from Tamaulipas. Six steers weighing ca. 250 kg were randomly assigned for each of six crosses: the susceptible (SS), resistant (RR), and the F1 (RS, SR) reciprocal crosses and F2 (RS x RS and SR x SR). The reciprocal crosses were made to evaluate maternal and sex linkage ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Compared with autosomally inherited traits, the sexlinked resistance may enhance or retard the rate of evolution of resistance (McDonald and Schmidt 1990;Daly and Fisk 1998). Tapia-Perez et al (2003) observed reduced egg mass weight in a pyrethroidresistant strain of B. microplus, which was suggested to be a resistance-related fitness cost. Within our laboratory conditions, the Santa Luiza strain had a higher reproductive capacity than the Mun˜oz strain, as demonstrated by the measured biological parameters ( Table 2).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Compared with autosomally inherited traits, the sexlinked resistance may enhance or retard the rate of evolution of resistance (McDonald and Schmidt 1990;Daly and Fisk 1998). Tapia-Perez et al (2003) observed reduced egg mass weight in a pyrethroidresistant strain of B. microplus, which was suggested to be a resistance-related fitness cost. Within our laboratory conditions, the Santa Luiza strain had a higher reproductive capacity than the Mun˜oz strain, as demonstrated by the measured biological parameters ( Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…The expected mortality of the F 2 generation of both type-I and type-II crosses at each amitraz concentration was estimated using the formula X = (0.25)W (S strain) + (0.25)W (F 1 type-I) + (0.25)W (F 1 type-II) + (0.25)W (R strain) . The relationships between the observed and expected mortality in both backcross and F 2 generations were analyzed by v 2 goodness-of-fit analysis, using procedures described by Tabashnik (1991) and Tapia-Perez et al (2003), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, no LC 50 was calculated. Tapia-Pérez et al (2003) have found that resistance to flumethrin is controlled by more than one gene without maternal effect. Conversely, our results, regarding the RS (RR♂×SS♀) strain resistance profile, do not support this statement, at least for flumethrin (100% mortality) and deltamethrin (100% mortality), because in both cases, the effective dominance of the mortality level was zero (D ML = 0) which means that inheritance of resistance is completely recessive when the male is resistant.…”
Section: Discussionmentioning
confidence: 99%
“…En general, un número bajo de garrapatas no causan un daño importante; de hecho, mantener bovinos en la explotación sin tratar con acaricidas, podría ser deseable para mantener poblaciones de garrapatas susceptibles (refugio), que al hibridarse con las resistentes, puedan eliminarse fácilmente (33) ; pero para ello es indispensable analizar en cada explotación, la cantidad de garrapatas presentes por bovino, ponderando el impacto económico de éstas sobre los costos corrientes de gestión. Los umbrales también proporcionan un punto de partida para conocer el estatus de la explotación, son números únicos, específicos para cada una.…”
Section: Figura 2 Umbrales Económicos El B Taurus Y B Taurus X B unclassified